PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS PADA MATA PELAJARAN IPA BIOLOGI SMP KELAS VII - Apriyanti, Meri; Arnentis, Arnentis; Natalina, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The research was held with purpose to develop classroom-based assessment on biology science for 7th grade Junior High School. Classroom-based assessment include paper and pencil test, attitude assessment, performance assessment, product assessment, project assessment, self-assessment and portofolio assessment. The development was conducted at Biology Education University of Riau and the limiting test at SMPN 1 Pekanbaru. The research held on January until April 2014. Research and Development with ADDIE model was implemented in this research. Subject of this research consisted of four Basic-Competency on the 7th grade Junior High School. Validation sheet was used as the data collection instrument. This validation sheet was filled by the internal dan external validator. Collected datas were analyzed by descriptive statistics. Average results of the validity of class-based assessment are: 3.6 for the paper and pencil test, 3.7 for attitude assessment, 3.9 for performance assessment, 3.7 for product assessment, 3.8 for project assessment, 3.7 for self-assessment and 3.8 for portofolio assessment. On the last stage of the research, a limiting test was held by using self-assessment questionnaires on the 7th grade Hang Lekir of SMPN 1 Pekanbaru and the number of students is 35. Based on the research’s results, the development of classroom-based assessment on biology science for 7th grade Junior High School student was done with the ADDIE model that consists of some phase, start from analyze, design, develop, and the last is implementation in a limiting test. Based on the results of validation, classroom-based assessment could be implemented with the field test.Key words: biology science junior high school, classroom-based assessment, development